Impact of International Financial Reporting Standards on the Quality of Accounting Measurement and Disclosure: A Field Study on Some Sudanese Banks - Hammad, Dr. Suleiman (The Gulf Economist, 2025)
The main objective of this study is to test the impact of international financial reporting standards (IFRSs) on the quality of accounting measurement and disclosure. In order to identifying the negative effects of practicing financial reporting methods that do not comply with international standards and their impact on the quality of accounting measurement and disclosure. The problem of the current study is represented in the multiplicity of accounting measurement and disclosure alternatives and their misuse by companies and individuals to maximize personal interests, in addition to the failure of some companies in adopting (IFRSs) and benefit from them to improve the quality of accounting measurement and disclosure. The researcher adopted inductive approach, descriptive analytical approach, and historical approach to conduct this study. To achieve the objectives of the field study, a number of (150) questionnaires were distributed to the study sample consisting of some employees in Sudanese banks in Gedaref, Kassala and Shendi, which represents the field study community, of which (139) questionnaires were returned, equivalent to (92.7%). After analyzing the field study data and testing the validity of the hypotheses, the study reached several results, including that the application of (IFRSs) contributes to improving direct measurement methods. The study results also showed that the application of (IFRSs) enhances the appropriate disclosure of accounting information. The study also concluded with a number of recommendations, the most important of which is the need to provide the appropriate economic and financial environment that allows the Sudanese banking sector to adopt (IFRSs). Keywords: IFRSs, Accounting Measurement Quality, Accounting Disclosure Quality